"Me Write Myself" The Free Aboriginal Inhabitants of Van Diemen's Land at Wybalenna, 1832-47 - Stevens, Leonie (Australian History, 2017)
Exiles, lost souls, remnants of a dying race ... The fate of the First Nations peoples of Van Diemens Land is one of the most infamous chapters in Australian history. The men, women and children exiled to Flinders Island in the 1830s and 40s have often been written about, but never allowed to speak for themselves. This book aims to change that. Documents penned by the exiles during their 15 years at the settlement Wybalenna offer a compelling counter-narrative to traditional representations of a hopeless, dispossessed, illiterate people's final days. The exiles did not see themselves as prisoners, but as a Free People. Seen through their own writing, the community at Wybalenna was vibrant, complex and evolving. Rather than a depressed people simply waiting for death, their own words reveal a politically astute community engaged in a 15 year campaign for their own freedom. This book tells a compelling story that will profoundly affect understandings of Tasmanian and Australian history.